Pengembangan Kemandirian Perempuan dalam Komunitas Pengrajin Anyaman di Kampong Caping Kota Pontianak - Nurma Afhiani, Syarifah (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2023)
Kampong caping is a tourist village with the majority of the work of the head of the household as day laborers and women or housewives as woven caping craftsmen, weaving activities have become a tradition for generations. The existence of the Kalimantan Idea Academy Community brings changes from ordinary villages to tourist villages by utilizing the empowerment of natural resources and human resources, as well as culture in it, this is supported by the presence of women caping craftsmen. The purpose of holding a research that focuses on analyzing the development of independence of women craftsmen who are members of the Kalimantan Academy of Craftsmen community, researchers want to dig deeper into the development of independence of women craftsmen. Descriptive research method with qualitative approach, data is collected by direct field observation, and primary data is collected by interviewing base informants, principal informants and key informants. The development of women's independence is able to be creative, meet the demand of buyer interest because of the uniqueness of caping decorations so as to produce caping craft innovations, women become independent and can help increase family income. Three aspects of women's independence are intellectual, social and economic aspects.